Pengaruh Penempatan Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Triwarga Dian Sakti (Honda Prima Harapan Indah) - Fira Amalia; Dian Meliantari (CV ODIS, 2023)
Dealers function as a distribution channel for producers and consumers. In order to thrive in the auto industry and compete with other dealers offering cars with their own advantages, car dealers, where new cars are sold, need to employ a variety of sound business methods. In recent years, the automotive sector in Indonesia has grown rapidly. This research aims to find out how the performance of employees at PT Triwarga Dian Sakti (Honda Prima Harapan Indah) is influenced by the variables of Job Placement (X1), Work Motivation (X2), and Work Environment (X3) on Employee Performance (Y). This study aims to determine the effect of Work Placement, Work Motivation, and Work Environment on Employee Performance at PT. Triwarga Dian Sakti Honda Harapan Indah Bekasi. With a total of 100 employees of PT. Triwarga Dian Sakti (Honda Prima Harapan Indah) was used as a research subject. data collection methods in this study used a questionnaire and a Likert scale. This research was processed using the Smart PLS 4.0 analysis method, the results showed that Work Placement and Work Motivation had a positive effect on Employee Performance, while the work environment did not have a significant effect on Employee Performance.